An Exploration Of Information Security Factors In Dwdm Transmission Systems For Telecommunications Infrastructure: A Case Study Of PT. XYZ - Afrursah Satrio Bia Pratama; Setiadi Yazid (UNIVERSITAS PAKUAN, 2026)
This study aims to explore the factors influencing the information security of the DWDM transmission system at PT. XYZ using a qualitative approach. The research was conducted through semi-structured interviews with experts directly involved in the operation of the DWDM network and analyzed using thematic analysis techniques with the assistance of ATLAS.ti. Technical parameters of optical networks such as OSNR, BER, and optical power were used to understand network conditions; ITU-T standards were used to map the architecture and assets of the DWDM transmission system; and the NIST SP 800-30 methodology was used to interpret the findings in the context of threats, vulnerabilities, and their impact on Confidentiality, Integrity, and Availability (CIA). The research results identified seven main groups of factors affecting the information security of DWDM transmission systems, namely Outside Plant (OSP) Security Issues, Inside Plant (ISP) Security Issues, Monitoring & Detection Limitations, Access Control & Configuration Weaknesses, Documentation, Policy & Governance Gaps, Environmental & Power Risks, and Incident & Preventive Weaknesses. These findings indicate that the information security of DWDM transmission systems is influenced by the interaction between technical and non-technical aspects; thus, this research is expected to provide an academic contribution and serve as a practical reference for PT. XYZ in enhancing the security resilience of its DWDM network.